2011
DOI: 10.7763/ijbbb.2011.v1.30
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Plasmodium knowlesi Infection in the Interior Division of Sabah, Malaysian Borneo

Abstract: Plasmodium knowlesi had been recognized as the fifth human malaria parasite due to its wide distribution of naturally acquired infection among the human populations in many parts of Southeast Asia. The aim of this molecular epidemiological study was to determine the incidence of human malaria parasites with special attention to P.knowlesi in four districts in the interior division of Sabah, Malaysian Borneo. Nested-PCR assays were used to identify the presence of Plasmodium species in the DNA extracted from 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Thirty-five infections diagnosed as P. malariae by microscopic examination were found to be P. knowlesi . This finding was similar to the studies carried out by other researchers in Malaysian Borneo [7,10,28,35], reporting that most microscopy-positive P. malariae infections were actually proven to be P. knowlesi infections when molecular approach was used. However, the transmission dynamics of this infection still remain unknown despite wide distribution of this parasite in Malaysian Borneo.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thirty-five infections diagnosed as P. malariae by microscopic examination were found to be P. knowlesi . This finding was similar to the studies carried out by other researchers in Malaysian Borneo [7,10,28,35], reporting that most microscopy-positive P. malariae infections were actually proven to be P. knowlesi infections when molecular approach was used. However, the transmission dynamics of this infection still remain unknown despite wide distribution of this parasite in Malaysian Borneo.…”
Section: Discussionsupporting
confidence: 91%
“…Note: The location of human P. knowlesi detected in this study is marked by triangles. Stars represented the distribution of this parasite reported by previous studies [10,35-38]. …”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Monkeys were positive with mono-infection of P. knowlesi. The prevalence of high incidence of P. knowlesi was among the patients in the age group of 21 to 40 years, more in males and in people who spent nights in forested areas for their lively hood (Lau et al 2011). In Singapore molecular epidemiological studies identified P. knowlesi infection in humans who visited forest and in longtailed monkeys from forests but not in monkeys from national reserve park (Jeslyn et al 2011).…”
Section: P Knowlesi Transmission Cycles and Its Site Of Transmissionmentioning
confidence: 99%
“…All the cases that were identified as P. malariae microscopically were identified as P. knowlesi by the nested polymerase chain reaction (PCR) that was developed by the investigators (Singh et al 1999(Singh et al , 2004. Identification of more cases in the following years from different hospitals in Sarawak (Cox- , high incidence in the interior divisions of Sabah (Lau et al 2011) and severe cases from a tertiary hospital in Sabah (Willam et al 2011) established that the entire Malaysian Borneo has P. knowlesi cases. Vythillingam et al (2008) reported cases from Peninsular Malaysia.…”
Section: Natural P Knowlesi Infections In Humansmentioning
confidence: 99%